Re-formulation zakat system as tax reduction in Indonesia - Hary Djatmiko (IAIN Salatiga, 2019)
Zakat is one of the Islamic financial instruments which is obligatory for every Muslim whose earnings reach the prescribed amount (nishab). On the other hand taxes must still be paid as an obligation of every citizen. Under the law, it is stated that zakat can be a deduction from taxable income. The aim of this research is to offer a more advanced concept, namely zakat can be a deduction from income tax. The technique used in this research is content analysis on the literatures discussing about zakat and tax in Islam. The results of this study suggest that zakat as a deduction from income tax has a greater impact than zakat as merely a deduction from taxable income. Zakat as a deduction from income tax will increase the impact of zakat in a larger economy. Zakat merupakan salah satu instrument keuangan Islam yang wajib ditunaikan oleh setiap umat muslim yang pendapatannya telah memenuhi jumlah yang ditentukan (nisab). Sedangkan, di sisi lain pajak harus tetap dibayarkan sebagai suatu kewajiban dari setiap warga Negara. Berdasarkan undang-undang, disebutkan bahwa zakat dapat menjadi pengurang penghasilan kena pajak. Tujuan penelitian ini ialah untuk menawarkan suatu suatu konsep yang lebih maju yaitu zakat dapat sebagai pengurang pajak penghasilan. Teknik analisis yang digunakan ialah analisis isi terhadap literatur-literatur terkait zakat dan pajak dalam Islam. Hasil penelitian menunjukkan bahwa zakat sebagai pengurang pajak penghasilan memiliki dampak lebih besar daripada jika zakat hanya sebagai pengurang penghasilan kena pajak. Zakat sebagai pengurang pajak penghasilan akan meningkatkan dampak zakat di dalam perekonomian yang lebih besar